Efficient Data Search System for Large-Scale Mobile Wireless Networks using Secured and Centralized Routing Protocol - George, Sulu; Azeez, Arifa (IJRDO -Journal of Computer Science Engineering, 2015)
This paper particularly addresses the data search problem in large-scale wireless networks with high mobility and density. Due to this, in a large scale network it is difficult to fetch the data from the nodes into a wireless network. Because of high overhead and difficulty of data discovery, the nodes will fail to fetch the data flexibly from the nodes and they cannot give the query service as we expect. Locality based distributed Data search system (LORD) is been used in the paper in order to overcome this problem. To increase the security and efficiency, we use Efficient Hybrid Routing protocol which reduces the complexity by minimizing the transmission time. Also backtracking algorithm is used for updating when one node moves into another region. The data will be published to a particular zone in a large network. When a user receives a metadata query from the user node, the file will be fetched directly from the particular centralized server and retrieves the data to the user.